2011
DOI: 10.1002/clc.20962
|View full text |Cite
|
Sign up to set email alerts
|

Small Heart With Low Cardiac Output for Orthostatic Intolerance in Patients With Chronic Fatigue Syndrome

Abstract: Background: The etiology of chronic fatigue syndrome (CFS) is unknown. Orthostatic intolerance (OI) is common in CFS patients. Recently, small heart with low cardiac output has been postulated to be related to the genesis of both CFS and OI. Hypothesis: Small heart is associated with OI in patients with CFS. Methods: Study CFS patients were divided into groups of 26 (57%) CFSOI(+) and 20 (43%) CFSOI(−) according to the presence or absence of OI. In addition, 11 OI patients and 27 age-and sex-matched control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…60 CFS with OI seems to constitute a well-defined and predominant subgroup of CFS. Small heart with reduced cardiac performance due to decreased preload may be an important target for the treatment of CFS.…”
Section: Discussionmentioning
confidence: 96%
“…60 CFS with OI seems to constitute a well-defined and predominant subgroup of CFS. Small heart with reduced cardiac performance due to decreased preload may be an important target for the treatment of CFS.…”
Section: Discussionmentioning
confidence: 96%
“…According to the literature, when compared to the controls, many CFS patients are characterized by orthostatic disorders and lower blood pressure, both possibly resulting from the abnormal functioning of ANS. Howev-er, to date, this phenomenon has not been fully elucidated [5,[7][8][9][10]. Using the Task Force Monitor might allow us to develop objective tools to diagnose CFS and perhaps allow us to diagnose it earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Recent small-sample studies about possible cardiac irregularities (Naschitz et al, 2006; Boneva et al, 2007; Burton et al, 2009; Hurwitz et al, 2009; Hollingsworth et al, 2011; Miwa and Fujita, 2011; Newton et al, 2011; Rahman et al, 2011; Beaumont et al, 2012) have motivated us to carefully examine whether HRV in persons with CFS may be substantially different from that in healthy controls. Given that previous studies have already tried to quantify the difference between the HRV of healthy control and CFS subjects using standard HRV metrics that assume stationarity, we have chosen two completely different multiscale methods, AFA and SDLE, that do not assume stationarity to analyze HRV, and used them on data from healthy control and CFS subjects in a highly non-stationary environment.…”
Section: Discussionmentioning
confidence: 99%
“…While no known biomarker for CFS has been identified to date, recent small-sample studies have suggested certain cardiac irregularities, such as low nocturnal HRV (Boneva et al, 2007; Burton et al, 2009; Rahman et al, 2011), small left ventricle and orthostatic intolerance (Miwa and Fujita, 2011), short QT interval (Naschitz et al, 2006), and low blood volume and diminished cardiac function (Hurwitz et al, 2009; Hollingsworth et al, 2011), are associated with CFS. It is not known if the cardiac irregularities are themselves a cause of the symptoms of CFS or if they are symptoms of the autonomic dysfunction and other systemic breakdowns which are more directly causative.…”
Section: Introductionmentioning
confidence: 99%